THE EFFECT OF COMPENSATION AND WORK MOTIVATION ON THE PERFORMANCE OF EMPLOYEES IN THE LIBRARY AND ARCHIVES SERVICE OF KARO DISTRICT - Binur (Lembaga Penerbit Penelitian Nusantara, 2025)
To get the best results from the existence of employees in the organization, it is necessary to define the right strategy, including thinking about how to manage employees so that they want to achieve the vision and mission of the organization. set out, and to create work motivation to achieve high performance and loyalty to the work of employees. The aim of this study was to know whether compensation and motivation at work affect performance. This study is a quantitative study, with a sample of 35 employees, with the results concluding that pay and work motivation have a significant effect in part on performance, which is highlighted by table t counts > t, after the test results, it is concluded that salary and work motivation have a simultaneous effect, this is shown by the calculated value F > table F. Wage and motivation work also provides almost all the variance values ​​of the performance variable, i.e. 87.9%. Based on the research results, the author suggests that leaders should care or develop policies related to compensation or ways to motivate employees. can increase employee loyalty and work capacity so it has a positive impact on performance